Collateral Formation After Repeated Transient Dearterialization of the Rat Liver. Issue 2 (1992) - Wang, Li-Qing; Persson, Bo G.; Bengmark, Stig
Abstract : Hepatic artery ligation is used for the palliation of patients with malignant liver tumours. Collaterals are developed rapidly and could to some extent explain why the growth is affected for only a short period. With intermittent dearterialization, collaterals seem to be avoided and possibly a more extended effect should be expected. The most efficient period of dearterialization to avoid collaterals was studied in this experiment. Five groups of rats were treated with daily repeated transient dearterializations for 0 (n = 3), 60 (n = 6), 120 (n = 6), 180 (n = 6) and 240 minutes (n = 6) respectively for 5 days and compared to another group (n = 3) that was permanently dearterialized. After treatment, celiac angiograms were obtained. All hepatic arteries were reliably occluded and patent after 5 days of daily blockades in all but two rats. There were no collaterals demonstrable on the angiograms in the first four groups after 5 days of intermittent obstruction of the arterial blood flow to the liver. After 240 minutes of dearterialization as well as after collaterals developed and were clearly demonstrated on the angiograms after six days. Liver enzymes were normal even after 4 hours of dearterialization. Repeated occlusions of the hepatic artery was reliably achieved with the implantable minioccluder. Repeated, transient dearterializations for 1, 2 or 3 hours could be performed without development of collaterals and without damage to the liver.